Metaphysical Foundation of African Epistemology: A Study of the Afemai-Etsako of Edo State in Southern Nigeria - Emmanuel Asia (University of Tabriz, 2021)
Truth and knowledge are essentially the dictates of some rationality or metaphysical ordainment. By sense experience man is capable of accounting for his past, contemplate his life and predict his future and all of reality, for traditional Africa, however (as is the case with most native societies), there is another mode of knowing beyond man’s immediate capacity in search of truth and reality. An analysis of this perception indicates that there is some metaphysical tinge to epistemology or knowledge claims—whether in the spheres of justice, morality/ethics, religion, political authority, prosperity, law, or ontology/world-view. Put on a plain pedestal: Isn’t there an African mode of knowing? By the study among the Afemai-Etsako of Southern Nigeria, this article tersely adumbrates the scope and nature of knowledge and discovers that, beside the common routes to it (experience and reason), the gamut of knowledge among the traditional Africans also have several metaphysical strands reducible to creative determinism, reactive interference, and representativeness in timing and naming.